Relevance of biological and biomechanical analysis in handball performance - Delamarche, P.; Bideau, B. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
In recent years there has been a remarkable expansion of sport sciences. The topic is now recognized both as an academic discipline and a valid area for sportsmen and coaches. The broad aim is to bring together scientists whose research work is directly related to handball and practitioners of handball interested in obtaining current information about the scientific aspects that are supporting the handball performance. Handball is a very complex intermittent game. This paper only focuses on some biological and biomechanical aspects of handball performance knowing that they contribute only for a part in team success. Anthropometric measurements, physiological, biological and biomechanical attributes, throwing velocity, strength and on-court performance are discussed. All these attributes can be advantageously used when planning adequate short and long-term training programmes able to enhance the team performance and to prevent individual injuries.